2009
DOI: 10.1590/s1517-83822009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of astrovirus and coronavirus in poults in the South Eastern Region of Brazil

Abstract: A survey of Turkey Coronavirus (TCoV) and Astrovirus (TAstV-2) prevalence was carried out from February to December during 2006 year in semiarid region of Brazil, from a turkey producer area, localized in South Eastern of Brazil. To asses the risk factor related to clinical material, climatic condition and type of RT-PCR applied, cloacal swabs (CS), faeces, sera, bursa of Fabricius (BF), thymus (TH) and spleen (SP) and ileum-caeca region were collected from 30-day-old poults suffering of enteritis episode char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(94 reference statements)
1
9
0
3
Order By: Relevance
“…Although CVP-2c has been detected in several Brazilian regions, this is the first description of its circulation in rural/wild areas representing human/wildlife interfaces ( Costa et al, 2005 ; Streek et al, 2009 ; Castro et al, 2010 ; Fontana et al, 2013 ; Oliveira et al, 2017 ). Despite of the availability and use of several commercial vaccines, viral enteritis − including that associated with CPV infection − remains an important problem for Brazilian dogs ( Oliveira et al, 2017 ).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Although CVP-2c has been detected in several Brazilian regions, this is the first description of its circulation in rural/wild areas representing human/wildlife interfaces ( Costa et al, 2005 ; Streek et al, 2009 ; Castro et al, 2010 ; Fontana et al, 2013 ; Oliveira et al, 2017 ). Despite of the availability and use of several commercial vaccines, viral enteritis − including that associated with CPV infection − remains an important problem for Brazilian dogs ( Oliveira et al, 2017 ).…”
Section: Resultsmentioning
confidence: 73%
“…Sequence analysis showed that 90.2% of the samples carried the amino acid (aa) Glu at the position 426, characteristic of CPV-2c strains, and 65% of these CPV-2c strains showed the substitution. Despite of the fact that CPV-2c was first described in South America in 2007, the high prevalence of CPV-2c strains in Brazil continues nowadays ( Pérez et al, 2007 ; Streek et al, 2009 ; Calderón et al, 2015 ; Fontana et al, 2013 ; Oliveira et al, 2017 ). Out of the 67 positive samples, 10% were identified as CPV-2a (KP694304) and 7% CPV-2b (KP694306) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies toward the investigation of PEMS have been reported elsewhere particularly in countries with intensive turkey breeding such as the USA and Brazil da Silva et al, 2009;Jindal et al, 2010;Mor et al, 2013;Moura-Alvarez et al, 2014), to the best of author's knowledge no study has been conducted on this subject in Turkey so far. The aim of this study was therefore to determine the presence and frequency of TAstV-2, TCoV and HEV in both PEMS-associated and clinically healthy meat-type turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…O coronavirus é um vírus envelopado com tamanho entre 50 e 160 ηm (RITCHIE et al, 1973;SPAAN et al, 2005) SIEBURTH; JOHNSON, 1957;TRUSCOTT, 1968;DESHMUKH et al, 1969;FREY, 1969). No entanto, somente em 1973 agentes semelhantes aos coronavírus puderam ser visualizados em ME no intestino de aves inoculadas com filtrados intestinais originados de aves acometidas pela doença HALL, 1973;RITCHIE et al, 1973 (GUY et al, 2000;YU et al, 2000;CARVER et al, 2001 (SELLERS et al, 2004;VILLARREAL et al, 2006;BUNGER et al, 2009;SILVA et al, 2009 (KAPCZYNSKI et al, 2002;CHAPPELL et al, 2005). Há pelo menos onze sorotipos de reovírus aviário classificados através da reação de neutralização viral (KAWAMURA et al, 1965;SAHU;OLSON, 1975;WOOD et al, 1980 Testes de neutralização viral foram amplamente utilizados na demonstração de diferentes sorotipos do vírus que podem afetar as aves (KAWAMURA et al, 1965;SAHU;OLSON, 1975;WOOD et al, 1980 JINDAL et al, 2008;JINDAL et al, 2010a).…”
Section: Coronavírusunclassified
“…A maioria das amostras apresentava a presença de mais de um vírus (69,7%) e se verificou que Astrovírus estiveram presentes em todas as amostras onde ocorreram associação de vírus. A elevada frequência de associação de vírus entéricos está de acordo com a literatura THEIL, 1985;JINDAL et al, 2009;JINDAL et al, 2010b) CHERRY, 2000b;VILLARREAL et al, 2006;SILVA et al, 2009). Nos Estados Unidos, Pantin-Jackwood et al (2007 (YU et al, 2000;CARVER et al, 2001;.…”
Section: Distribuição Geográfica Das Amostrasunclassified